ASSOCIATIONS OF INFLAMMATORY CYTOKINES WITH CHOROIDAL NEOVASCULARIZATION IN HIGHLY MYOPIC EYES. Issue 2 (February 2015) - Yamamoto, Yukimi; Miyazaki, Dai; Sasaki, Shin-ichi; Miyake, Ken-ichiro; Kaneda, Shuzo; Ikeda, Yoshifumi; Baba, Takashi; Yamasaki, Atsushi; Noguchi, Yumiko; Inoue, Yoshitsugu
Abstract : Purpose: To determine the relationships between the levels of intraocular inflammatory cytokines and the clinical characteristics of myopic choroidal neovascularization (mCNV) in eyes with myopic maculopathy. Methods: One hundred eyes of 100 cases, including 51 mCNV eyes, 14 highly myopic eyes without choroidal neovascularization, and 35 normal subjects, were studied. The intraocular levels of choroidal neovascularization-related cytokines, like vascular endothelial growth factor, MCP-1, IL-8, IL-10, and IL-23, were determined. Results: The levels of vascular endothelial growth factor and IL-8 were significantly higher in eyes with mCNV than in high myopia eyes without mCNV with significant odds ratio of 2.00 and 2.25 per quartile, respectively ( P < 0.05). When myopic lesions of patients with mCNV were classified into 3 categories based on the severity, IL-8 and MCP-1 were significantly elevated depending on the presence of maculopathy (P < 0.05). Vascular endothelial growth factor was significantly elevated in eyes of Category 2. An advancement of the maculopathy category was significantly associated with the need for multiple treatment of intravitreal bevacizumab ( P < 0.05). In 12 eyes that required multiple intravitreal bevacizumab, the MCP-1 level was significantly elevated. Conclusion: The significant associations of mCNV in highly myopic eyes with elevated levels of vascular endothelial growth factor or inflammatory cytokines and maculopathy lesions strongly suggest an involvement of inflammation in the etiology of mCNVs. Abstract : The levels of vascular endothelial growth factor and IL-8 were significantly higher in eyes with than without a myopic choroidal neovascularization. MCP-1 had a significantly elevating trend depending on the development of maculopathy in patients with myopic choroidal neovascularization and was associated with refractoriness to intravitreal bevacizumab injection.